Veevers, D. (2023). The Great Defiance: How the world took on the British Empire. Ebury Press, Penguin Random House (502 pages). Hardback ISBN: 9781529109955. Trade Paperback ISBN: 9781529913644 - Leontidou, Lila (The Greek Review of Social Research, 2024)
N/A